Abstracts presented at the 3rd National Non-Communicable Diseases Scientific Conference at Arusha International Conference Center in Arusha, Tanzania (Tanzania Medical Journal, 2022)
Tanzania Medical Journal is proud to be collaborating with the Organizing committee of the 3rd National Non-Communicable Diseases Scientific Conference in publishing the abstracts presented at the conference that was held on 11th - 12th November 2021, at the Arusha International Conference Center, Arusha, Tanzania. The conference theme was: “Multisectoral Engagement and Collaboration in addressing Non-Communicable Diseases”. The abstracts are listed along with authors’ affiliations. The scientific committee for this conference was responsible for peer review of the abstracts.